Comparison of Pin Tract Infection Rate in Buried Versus Unburid Krischner Wires Fixation in the Management of Gartland Type III Supracondylar Fracture of Humerus in Children - Noman Khan, Hussain Bux Palh, Najeeb u rehman kalhoro, Sajjad Hussain Bhatti, Muhammad Hamayun Hameed, Abdul Samad Qureshi (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: One of the most common injuries of the elbow in children is called supracondylar humerus fracture. It makes up around 18% of all fractures in children and 60% of all elbow fractures. The children in which these fractures happen are aged from 5 years to 7 years. This injury happens when a child falls on a n outstretched hand and the elbow is bent backwards too far (hyperextension). The side effects of this fracture are pain, swelling, and a limited range of motion in the injured elbow. In more serious fractures where the arm is displaced, it looks like an elbow dislocation in younger children and the arm may look S-shaped. To treat displaced supracondylar humerus fractures, either closed or open reduction is done. After this, Kirschner wires (K-wires) are inserted through the skin to hold the bone in place. Most of the time this method is used because of its cost-effectiveness and it is also less invasive. Objective: To compare the infection rates between unburied and buried K-wire fixation to treat Gartland Type III fractures in young children Study Design: A prospective, randomised controlled study Duration and Place of Study: this study was conducted in Memon Medical Institute Hospital Karachi from April 2024 to April 2025 Methodology: This study is a randomised controlled study which was performed in the Orthopedic and Trauma Department. There were a total of 100 participants included in this research. All of the participants were young children of both genders who were aged between 2 years to 12 years. All the children were having humeral supracondylar fractures of the Gartland Type III which were less than 48 hours old. These fractures were without any signs of neurovascular compromise. Children were admitted and evaluated clinically after the radiological confirmation of a supracondylar fracture. Demographics of the participants along with mechanisms of injury were recorded. SPSS version 25 was used to analyse the data. Continuous variables and age were expressed in terms of mean and standard deviation. The correlation between infection rates were assessed using the chi-square test. Results: There were a total of 100 participants included in this research. All of the participants were young children of both genders who were aged between 2 years to 12 years. All of the participants were equally divided into 2 groups. One group had fixation with buried K-wires (n=50) while the other had fixation with unburied K-wires (n=50). Males were more likely to receive unburied K-wires (68%). The highest number of children were from the age group of 9 to 12 years (n=37). Most of them received unburied K-wire fixation (56%). Conclusion: The risk of pin tract infection was lower with buried K-wire fixation in children with humeral supracondylar fractures of the Gartland Type III.